Holistic soil health indicators and measurement protocols - Accelerating Impacts of CGIAR Climate Research for Africa; CIFOR-ICRAF; Coalition of Action for Soil Health (2025)
This poster gives examples of soil health indicators and associated measurement protocols. Tracking indicators helps to improve understanding of soil status and the impact of restoration efforts on soil health over time. The poster emphasises a holistic approach to soil health monitoring integrating physical, livelihood and social, biological, chemical, and land use indicators.